2020
DOI: 10.1007/s13555-020-00431-6
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic and Clinical Response Predictor Factors in Nonsegmental Vitiligo Treated with Narrowband Ultraviolet B Phototherapy: A Prospective Observational Study

Abstract: Introduction: Few data on possible local factors that can influence the achievement of response in nonsegmental vitiligo (NSV) treated with narrowband ultraviolet B (Nb-UVB) phototherapy are available. Our objective is to evaluate possible correlations between therapeutic outcomes and dermoscopic and local (lesional) clinical findings of vitiligous lesions undergoing Nb-UVB phototherapy to find positive and/or negative response predictor factors to such treatment. Methods: For each target patch, we calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 30 publications
(64 reference statements)
2
22
1
Order By: Relevance
“…That finding was confirmed in a study on patients suffering from segmental vitiligo treated with either medical (phototherapy or laser therapy) or surgical treatments [47], yet it was not seen in another study investigating patients with non-segmental vitiligo treated with ultraviolet B phototherapy, which only found a correlation between positive response and dermoscopic evidence of perifollicular pigmentation at baseline (Fig. 10) [48].…”
Section: Pigmentary Dermatosesmentioning
confidence: 86%
See 1 more Smart Citation
“…That finding was confirmed in a study on patients suffering from segmental vitiligo treated with either medical (phototherapy or laser therapy) or surgical treatments [47], yet it was not seen in another study investigating patients with non-segmental vitiligo treated with ultraviolet B phototherapy, which only found a correlation between positive response and dermoscopic evidence of perifollicular pigmentation at baseline (Fig. 10) [48].…”
Section: Pigmentary Dermatosesmentioning
confidence: 86%
“…Finally, dermoscopic examination has also been shown to be useful to predict therapeutic outcomes [46][47][48]. In particular, a recent study showed a reduced response rate to excimer laser therapy of non-segmental vitiligous lesions Fig.…”
Section: Pigmentary Dermatosesmentioning
confidence: 99%
“…Given that recent research showed that preservation of perifollicular pigmentation under dermatoscope ( 47 ), we evaluated if there were more residual melanocytic biomarkers in lesions of good therapeutic response or short duration. As shown in Figure 2 , all of the melanocyte marker genes showed a trend of higher residual level of expression in good response and short duration lesions, the degree of higher expression did not reach the level of statistical significance (p>0.05, two tailed t test), suggesting the level of residual melanocytic marker genes cannot be reliably used to predict therapeutic response.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between lesional skin pigmentation and the patient’s therapeutic response to vitiligo therapy has been unclear as the existing literature provided conflicting conclusions. On the one hand, vitiligo lesions with peri-follicular pigmentation under dermatoscope is associated with more favorable response ( 47 ). On the other, the degree of depigmentation in general did not show correlation to NBUVB therapy ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Errichetti et al note the presence of several features on dermoscopy that are often not visualized by the unaided eye and thus not appreciated clinically. 49 In this study, 70 vitiliginous patches were visualized both dermoscopically and clinically. 49 Perifollicular pigmentation was noted in 21.4% of the lesions when evaluated under dermoscopy and only 4.3% when evaluated clinically.…”
Section: Vitiligomentioning
confidence: 99%